KARAKTERISTIK FUNGSIONAL DAN UJI HEDONIK KUKIS KETAWA BERBAHAN DASAR TEPUNG GANDUM UTUH LOKAL - Palimbong, Sarlina; Suyanto, Mykhel; Febriyanti, Maria; Angel, Cecilia; Banjarnahor, Dina; Nirmalasari, Damara (Fakultas Pertanian Universitas Alkhairaat Palu, 2023)
Laughing Cookies are a traditional snack made from local whole wheat flour (Gaul). Cookie dough added with kimpul flour is one of the innovative efforts to process the abundant kimpul commodity in Cukilan Village, Semarang Regency, Central Java. This study aimed to determine the panelists' functional characteristics and level of preference for the laugh cookies made from local whole wheat flour. The laugh cookies are made with three formulations, namely A (1:0), B (1:1), and C (1:2) (Gaul flour: kimpul flour ratio). The results of the hedonic test with the parameters texture, color, aroma, taste, and overall showed that the fifty panelists liked formulations A, B, and C, respectively, with a score of 3.7-3.8 respectively (neutral – somewhat like); 3.1-3.6 (neutral – somewhat like), and 2.9-3.4 (dislike - neutral). Based on the panelists' preference for Formulations A and B, these two formulas were tested for fiber. The crude fiber content in formulations A and B was 42.74% and 46.22%, respectively. Based on the study's results, it can be concluded that the formulation of the laugh cookies has a different effect on the level of preference and crude fiber. The best treatment was formulation A, with the highest preference level and high oil fiber.